Reminiscing The Heritage of The Old Indian Mosque in Kuching, Sarawak - Mos, Mitchell Tony; Sebri, Nur Izzati; Husaini, Nur Atiqah (MAJ - Malaysia Architectural Journal, 2025)
Measured drawings are architectural drawings drawn based on measurements on existing building sites, usually involving historical buildings. The Old Indian Mosque (Indian Mosque) which was built in the 1830s is one of the few remaining traditional mosques in Sarawak which still preserves its original design and function. This research aims to analyse the cultural and social implications of the mosque on the Kuching community. The objectives of the study are to collect historical information, including the measurement of the Old Indian Mosque to produce detailed architectural drawings and report based on the data collected. The methodology applied in this study consists of interpretation of building through in-depth analysis; supported by measured drawings and historical assessment. The findings of this study show that the architecture of the Old Indian Mosque represents a significant heritage of mosque architecture in Southeast Asia. The study also shows that there is a strong relationship of the design, form, construction method and material that binds with the local context, climate and culture in Kuching, Sarawak. In conclusion, further research on traditional mosques specifically in Sarawak should be further explored and documented as part of the architectural heritage in Southeast Asia, for future reference.